(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The paper discusses the importance of soft skills in higher education, with a focus on foreign language instruction, and offers practical suggestions for incorporating soft skills into language learning classes. Soft skills refer to a set of personal attributes and interpersonal abilities that enable individuals to interact effectively with others. These skills are often related to emotion al intelligence and are crucialfor success in both personal and professional settings.